2021
DOI: 10.1111/aogs.14144
|View full text |Cite
|
Sign up to set email alerts
|

Mental health among postpartum women during the COVID‐19 pandemic

Abstract: We read with great interest the article by Ceulemans et al. 1 on maternal mental health issues during the COVID-19 pandemic. We would like to provide some additional insights from our recent interviews with 21 postpartum women during the pandemic to triangulate and support these quantitative findings. Interviews were

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 5 publications
3
2
0
Order By: Relevance
“…These findings were supported by our qualitative data which indicated that gym closures, reduced access and/or unwillingness to utilize childcare options, and working from home arrangements all impacted the ability of women to partake in formal or organized physical activity. Similar experiences were reported in the qualitative study by Lim et al, also in postpartum women ( 38 ). This reduction in activity levels could signify potential ramifications of the pandemic on the physical health of women following a HDP.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These findings were supported by our qualitative data which indicated that gym closures, reduced access and/or unwillingness to utilize childcare options, and working from home arrangements all impacted the ability of women to partake in formal or organized physical activity. Similar experiences were reported in the qualitative study by Lim et al, also in postpartum women ( 38 ). This reduction in activity levels could signify potential ramifications of the pandemic on the physical health of women following a HDP.…”
Section: Discussionsupporting
confidence: 88%
“…Our study did not find a significant difference in mental health outcomes reported by women by COVID-19 lockdown status, in contrast to findings from survey studies conducted in countries including the US, Canada, Mexico, Belgium, Italy and Qatar, all of which report heightened postpartum depressive and anxiety symptoms (8,9,(34)(35)(36)(37) during the local peak of COVID-19 compared to pre-COVID. To our knowledge there has only been one qualitative study (38), conducted in Australia, in which semi-structured interviews with postpartum women supported the findings of increased depressive and anxiety symptoms reported in previous quantitative studies. Although not statistically significant, women in our study meeting the threshold for significant depression symptoms increased and anxiety symptoms almost doubled during or following any lockdown.…”
Section: Discussionsupporting
confidence: 69%
“…However, the described feelings of isolation, fear of COVID-19, and changes to everyday life were unique to the pandemic and have the potential to exacerbate stress and anxiety. This is a similar finding by Lim et al (2021) who found that the cancelation of important events, having to stay at home for much of the time and fear of getting sick could have an impact on maternal mental health. The researchers also found altered sleep and eating patterns to be significant, which were not described in the present study.…”
Section: Discussionsupporting
confidence: 81%
“…The sample consisted of 163 mothers, 74 (45.4%) were first time mothers (Ostacoli et al, 2020). Lim et al, (2021) found that the mothers reported negative mood related to isolation and lack of exercise and poor sleep.…”
Section: Introductionmentioning
confidence: 99%
“…The mobile application-based perinatal interventions evaluated in the included studies of this review were found to be feasible and viable methods of improving parents’ parenting outcomes, which is encouraging as parents have had to rely more on technology-based resources for perinatal support during the COVID-19 pandemic ( Cameron et al, 2020 ). Recent studies have shown that many parents (especially mothers) have chosen to isolate themselves to avoid COVID-19 infection, leading them to receive insufficient perinatal support from healthcare professionals, friends, and family ( Ceulemans et al, 2021 ; Lim et al, 2021 ). This puts them at higher risk of developing psychological problems during the perinatal period ( Ceulemans et al, 2021 ; Molgora & Accordini, 2020 ; Thapa et al, 2020 ), with more mothers experiencing perinatal depressive and anxiety symptoms during the COVID-19 period compared to the pre-pandemic period ( Hessami et al, 2020 ; Lebel et al, 2020 ; Suwalska et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%